2011
DOI: 10.1007/s11172-011-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Cp2ZrCl2-Catalyzed cycloalumination of acetylenic alcohols and propargylamines by Et3Al

Abstract: The Cp 2 ZrCl 2 catalyzed cycloalumination of acetylenic alcohols and propargylamines by Et 3 Al was studied. The process affords 2,3 disubstituted alumacyclopent 2 enes, which were identified by the analysis of the products of their deuterolysis and hydrolysis. The cycloalumi nation of alkyl and phenyl substituted propargylamines proceeds with high regio and stereo selectivity to give the corresponding allylamine derivatives in high yield. Unlike the phenyl derivatives, the cycloalumination of alkyl substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Apparently, in the case of propargylic alcohols, the formation of high-molecular-weight compounds is attributed to the polymerization of niobium-containing allene, which is generated via the β-elimination of the alkoxide group of the niobiacyclopropene intermediate. Previously, we have found that the Zr-catalyzed cycloalumination of substituted propargylic alcohols was also accompanied by the polymerization as the side reaction caused by the β-elimination of the alkoxide group [ 56 ]. However, the reaction of substituted homopropargylic alcohols 4 with four equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, in the case of propargylic alcohols, the formation of high-molecular-weight compounds is attributed to the polymerization of niobium-containing allene, which is generated via the β-elimination of the alkoxide group of the niobiacyclopropene intermediate. Previously, we have found that the Zr-catalyzed cycloalumination of substituted propargylic alcohols was also accompanied by the polymerization as the side reaction caused by the β-elimination of the alkoxide group [ 56 ]. However, the reaction of substituted homopropargylic alcohols 4 with four equiv.…”
Section: Resultsmentioning
confidence: 99%
“…strates that αor β-heteroatom-substituted alkynes react much more promptly than internal aliphatic alkynes, and thus enhances significantly the synthetic scope of the transformation by disclosing an efficient access to some heteroatom-functionalized alkenes with control of the double-bond geometry. The study represents an improvement over previous works on Zr-catalyzed cycloalumination of propargylamines 21 and alkynylphosphines 22 because the current catalytic system consisting of Et 2 Zn, Ti(O-iPr) 4 , and EtMgBr is more practical and less costly. Moreover, the dizincated species offer more potential for subsequent functionalization than the dialuminated species.…”
Section: Letter Syn Lettmentioning
confidence: 93%
“…Meanwhile, it is known that 1-alkynylphosphines, 1-alkynylphosphonates, propargylamines, 1-alkynyl selenides, and 1-alkynyl sulfides are efficient substrates for the preparation of zirconacyclopentenes [17][18][19][20] and aluminacyclopentenes. [21][22][23][24] Regarding 2-zincoethylzincation, only one case of the preparation of organozinc derivative in 63% yield only after 4 days using the Ti-Mg-catalyzed reaction of 5decyne with Et 2 Zn has been reported in the literature. 25 However, this reaction is a unique example of carbozincation of the triple carbon-carbon bond with Et 2 Zn using oxidative coupling of ethylene and 5-decyne on titanium(II) in catalytic cycle.…”
mentioning
confidence: 99%
“…46 Generally, it is consistent with our earlier views about the key role of zirconocene-ethylene intermediate in this reaction. 47 While considering the Zr-catalyzed reaction of Et 3 Al with propargyl alcohols, propargylamines, 37 and 1-alkynylphosphines, 38 we suggested that the Et 2 AlCl molecule located in the zirconacyclopropene coordination sphere is the principal factor determining the regioselectivity of cycloalumination. Similarly, in the case of cycloalumination of 1-alkynyl selenides, one can assume the formation of stable five-membered cyclic complex (Scheme 2).…”
Section: Scheme 1 Zr-catalyzed сYcloalumination Of 1-alkynyl Selenidementioning
confidence: 99%
“…33,34 Successful results on the selenation of cyclododecyne and cyclododeca-1,5-diyne cycloalumination products with selenium at elevated temperature have been reported. 35,36 As an alternative, recently we developed regio-and stereoselective methods for the preparation of О-, N-, and P-containing alkenes by Cp 2 ZrCl 2catalyzed cycloalumination of propargyl and homopropargyl alcohols, propargylamines, 37 and 1-alkynylphosphines. 38 The efficiency of carboalumination for the synthesis of P-and S-containing alkenes was demonstrated by Cp 2 ZrCl 2 -catalyzed ethylalumination of 1-alkynyl phosphorus oxides 39 and methylalumination of alkynyl sulfones, sulfoxides, and sulfides.…”
mentioning
confidence: 99%